Unjuk Kemampuan Catalytic Converter Dengan Katalis Tembaga Dalam Mereduksi Konsentrasi Emisi Gas Buang Toyota Kijang Innova - Warju, (Teknika, 2008)
The aims of this experiment are firstly to conduct a catalytic converter secondly, to find out to what extend copper (Cu) as catalyst is efficient. To measure the concentration of carbon monoxide (CO) and hydrocarbon (HC) on frame there are two conditions  required. First is when the standard condition, and second is when Cu catalytic converter is applied using gas analyzer. This experiment results in the fact that the use of Cu catalytic converter reduces the production of CO and HC of pertamax automobile.